Proceedings of the 28th International Workshop on Vertex Detectors — PoS(Vertex2019) 2020
DOI: 10.22323/1.373.0027
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor removal - Displacement damage effects involving the shallow acceptor doping of p-type silicon devices

Abstract: New sensor technologies are under development to cope with the ever increasing requirements for high energy physics (HEP) detectors. For the High-Luminosity LHC (HL-LHC) and the Future Circular Collider (FCC) higher radiation hardness, improved timing performance and lower cost large area detector technologies are essential. Recent developments of p-type silicon planar sensors, sensors with intrinsic gain for timing applications and monolithic sensors are examples for next generation detector technologies. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…a BiOi concentration of 10 13 cm -3 will generate a 2 pA current at 293 K). 0.0 5.0x10 13 1.0x10 14 1.5x10 14 2.0x10 14 0.0 0.5 The dependence of the BiOi introduction rate on the boron doping concentration, as deduced by C-V measurements, is given in Figure 4. A non-linear dependence on boron content was reported earlier by Vines et al [45].…”
Section: -Dlts Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…a BiOi concentration of 10 13 cm -3 will generate a 2 pA current at 293 K). 0.0 5.0x10 13 1.0x10 14 1.5x10 14 2.0x10 14 0.0 0.5 The dependence of the BiOi introduction rate on the boron doping concentration, as deduced by C-V measurements, is given in Figure 4. A non-linear dependence on boron content was reported earlier by Vines et al [45].…”
Section: -Dlts Investigationsmentioning
confidence: 99%
“…In this respect the estimation of defect introduction rate through its A configuration, of gBiOi A = 0.023 cm -1 in this case, is regarded to be the minimum value, as gBiOi should be calculated considering both defect configuration (gBiOi= gBiOi A + gBiOi B ). 1.2x10 13 1.4x10 13 1.6x10 13 1.8x10 13 2.0x10 13 2.2x10 13 2.4x10 Bistable defects have normally more than one stable state which, under certain conditions may reversibly pass over from one state to another and so change their spatial and electronic structure [46][47][48][49]. There are several examples of radiation induced metastable centers in Silicon, some with bistable character (see the [50] review), and not always the different possible electronic states of the defect could be evidenced on the same samples on which the metastability was first detected or with the same investigation techniques.…”
Section: -Dlts Investigationsmentioning
confidence: 99%
“…The gain almost vanished at irradiation fluences of about 10 15 cm −2 . The effect is attributed to the effective acceptor removal in the gain layer [32]. By means of SIMS measurements [33] it has been shown that the boron ion is in the same position as before irradiation, and most likely inactivated by becoming interstitial and forming defect complexes with oxygen.…”
Section: Radiation Hardening Of Low-gain Avalanche Diodesmentioning
confidence: 99%
“…[43] However, further work is required to form a full understanding of the microscopic defect formation kinetics causing acceptor removal. [44] Besides the introduction of newer phenomena such as acceptor removal, the validity of traditional radiation damage models is not verified for extreme fluences of > 1×10 16 n eq /cm 2 -for example, a saturation of radiation effects at very high fluences has been observed. [28,45] More extensive research, both experimental and in simulation, is required to determine and quantify the underlying physics behind these observations.…”
Section: 3 Center Rightmentioning
confidence: 99%